Resistance Messages Against Capitalism in the Rempug Tarung Adu Tomat Cultural Event by Tomato Farmers in Cikareumbi Village - Reza, Faisal; Sugiarta, Nugraha (Communication In Research And Publications, 2025)
This study examines the resistance message against capitalism conveyed by tomato farmers in Cikareumbi Village, Lembang Sub-district, through the cultural tradition of Rempug Tarung Adu Tomat (Tomato Battle). Using a qualitative approach within a critical discourse framework, the research explores how farmers employ symbolism to express collective resistance. The findings show that the resistance is articulated in two stages: first, by deliberately allowing tomatoes to rot as a rejection of unfair pricing; and second, by staging the Tomato Battle as a symbolic protest. Key symbolic elements include the masked guards representing capitalist oppression, the masks themselves symbolizing deception, and the tomato battle signifying solidarity and unity among farmers. Furthermore, the processing of rotten tomatoes into compost and seeds highlights their pursuit of independence from exploitative systems. This resistance is driven by two main factors: the unfair pricing practices imposed by intermediaries and the lack of government support. Ultimately, the farmers’ message reflects not only their opposition to capitalist exploitation but also their demand for fair recognition and state intervention.